Analysis of low-carbon rice farming behavior and its influencing factors in farmers under the distributed cognition perspective—empirical study based on 2,173 farmers in Jiangxi Province - Huang, Qinglong; Chen, Meiqiu; Zhang, Ting; Zhang, Fulin; Zhang, Jie (Frontiers in Sustainable Food Systems, 2024)
Rice production is the core component of the food security strategy in China, but it is also a major source of methane and nitrous oxide. Promoting low-carbon rice farming (LCRFs) to increase the carbon sink, decrease carbon emissions, and achieve low-carbon, high-yield production is an inevitable “win-win” choice for achieving “double carbon” targets and guaranteeing national food security. Evaluation of the current acceptance status of LCRFs behavior among farmers and analysis of the LCRFs behavioral patterns and influencing factors was performed based on distributed cognition theory. This study contributes to the advancement of research on farmers' adoption decisions and fills gaps in LCRFs technical research on farmers' decision-making behavior. The results also provide a basis for formulating policies to encourage LCRFs and protect cultivated land. In this study, we investigated 2173 farmers in Jiangxi Province and employed a multivariate ordinal logistic model. The results of the study showed that: 1) the overall acceptance of LCRFs behavior is currently not very high. In the 2173 questionnaires, the mean number of LCRFs behavior items accepted by farmers was 3.10 items; 153 farmers did not adopt any LCRFs behavior, and only 77 farmers adopted all LCRFs behaviors. Most farmers (n=535) adopted three LCRFs behaviors. 2) In distributed cognition affecting LCRFs behavior, acceptance was primarily affected by cultural forces, followed by local forces, while the effects of personal forces were limited.Therefore, it is recommended that training and promotion should be increased, policy subsidies should be increased, the land market should be improved, and LCRFs demonstrations should be carried out to increase the acceptance of LCRFs behavior among rice farmers.